Quality Attributes and Sensory Acceptance of Different Botanical Coffee Co-Products - Katarína Poláková; Alica Bobková; Alžbeta Demianová; Marek Bobko; Judita Lidiková; Lukáš Jurčaga; Ľubomír Belej; Andrea Mesárošová; Melina Korčok; Tomáš Tóth (Foods, 2023)
Coffee processing is a major contributor to the creation of food and product waste. Using coffee co-products can play an essential role in addressing environmental problems and issues with nutritionally unbalanced foods, population growth, and food-related diseases. This research aimed to determine the quality and sensory parameters (aw, pH, dry matter, TAC, TPC, fat, fatty acids profile, fiber, caffeine, chlorogenic acids, color, and sensory analysis) of different botanical origins of cascara (coffee husks) and silverskin (thin layer). The results of this study show that silverskin and cascara are a good source of TAC (1S 58.17 ± 1.28%, 2S 46.65 ± 1.20%, 1C 36.54 ± 1.84%, 2C 41.12 ± 2.11%). Cascara showed the presence of polyphenols (2C 49.135 g GAE·kg−1). Coffee co-products are good sources of fiber. Silverskin had higher values of caffeine than cascara. Palmitic, stearic, oleic, linoleic, and arachidic acids were the most represented acids in the samples. Given the obtained results, cascara can be considered “low-fat” (1C 4.240 g·kg−1 and 2C 5.4 g·kg−1). Based on the sensory evaluation, no sample reached the acceptable index value of 70%. Understanding the link between the character, identification properties, and composition of coffee co-products of different botanical origins can enable their application in the food industry.